Distributed object-based software environment for urban system integrated simulation under urban-scale hazard?Part I Infrastructure. - Serror, M. Hassanien
In this paper, a distributed object-based software environment (DOSE) has been developed to facilitate the integrated simulation of an urban system under the risk of urban-scale hazards such as earthquakes. It is understood that individual simulation participants perform their simulation services in separate environments, bartering service exchange relationships to get what they need to resolve their part of the problem. This is the communication gap between the scientists on one side and the end users who need to understand knowledge and employ it on the other side. The authors envision a distributed simulation service software environment running in parallel with the activities of simulation participants. DOSE has lent itself to integrate interdisciplinary participants through an infrastructure that has three basic building blocks, namely: modularity, scalability, and interoperability. The modular, object-based, design of DOSE architecture is described in terms of key functionalities of four distinct layers, namely: resource, core, domain, and interface layers. DOSE scalability in terms of urban system size and participant third-party application complexity is enabled through the interface layer. A message passing model is developed using the Message Passing Interface standard and a control room is provided to schedule the interaction/communication among model processes. DOSE interoperability with the vulnerability analysis third-party applications is enabled through the Industry Foundation Classes (IFC) standard. An adopted analogy between DOSE and construction industry is employed to provide interpretation and implementation for DOSE interoperability. While interfacing IFC object model to solve DOSE interoperability questions, an extension model for the structural view of IFC is proposed and accepted by the International Alliance for Interoperability. The DOSE application for real-world urban systems is beyond the scope of this paper and is presented in an accompanying paper work.
Keywords: Integrated simulation; Urban system; Urban-scale hazard; Modularity; Scalability; Interoperability